Experiments to illustrate the resonance frequency in a quartz crystal microbalance with low cost materials - Balladares, Julio David Gonzales (2024)
This study proposes three activities for a multidisciplinary laboratory practice with university students of advanced cycles, these didactic activities seek to develop scientific curiosity through the construction of an analytical instrument. To this end, students assemble a microbalance with low-cost frequency meters by replacing the oscilloscope with smartphones, DIY frequency counters, and Arduino development boards, for the educational purpose of illustrating the piezoelectric properties of quartz crystal and its relationship with the resonant frequency by experiential learning.